Industrial Thumb Injuries – A Review of 63 Cases - P. S. Chari; S. K. Soni (Indian Journal of Plastic Surgery)
Sixty three patients with thumb injuries caused in industrial accidents have been review d. Some of the factors bearing on such injuries have been briefly discussed.